Entitas Konten Pendidikan dalam Mengawal Ritme Kebijakan Terbaru Terhadap Peningkatan Kualitas Pendidikan di Kabupaten Buleleng - I Made Sedana (Edukasi: Jurnal Pendidikan Dasar, 2022)
The existence of equitable access and improving the quality of education makes Indonesian citizens have life skills so as to encourage the establishment of full human development as well as civil and modern society imbued with the values of Pancasila. With several studies, it is hoped that the progress of education that is adapted to the times and the competencies that fulfill it can prepare for the regeneration of regional human resources, especially in Buleleng Regency which is superior, dignified and characterized so that educational content entities in guarding the rhythm of the latest policies have an effect on improving the quality of education in Buleleng Regency.